GAMBARAN PENGETAHUAN TENTANG PENCEGAHAN LUKA DM PADA ANGGOTA KELUARGA PASIEN DM DI WILAYAH KERJA PUSKESMAS TANJUNG BATU OGAN ILIR - Utami, Utami; Anggraini, Dini; Eliani, Ovi (Journal Safety and Healthty, 2024)
Diabetes mellitus (DM) is a chronic and non-communicable disease with a high risk that causes serious problems throughout the world. The purpose of this study was to look at the description of knowledge about DM wound prevention in family members of DM patients in the Tanjung Batu Ogan Ilir Health Center Work Area. This research was carried out in the working area of the Tanjung Batu Timur Health Center in 2019 using a Cross Sectiona design. In this study, the population taken were family members of DM patients who had been recorded to come to Tanjung Batu Health Center with total sampling technique. The results of the study were that the age ranged from 18 to 63 years, the percentage of sex between men and women were 32% and 68%, respectively, the majority of research respondents based on respondents who lived with DM patients were children (blood ties), and the percentage the largest based on the respondent's education level is high school education / equivalent, and the percentage of work status of research respondents both working and not working as much as 44% and 56%, respectively. The results of this study can be used as a reflection to improve and improve the performance of existing programs related to DM in the working area of the Puskesmas.